2000
DOI: 10.1002/(sici)1097-4628(20000228)75:9<1149::aid-app8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of an acrylics-grafted polyester and its aqueous dispersion?mechanical properties of acrylics-grafted polyesters

Abstract: Mechanical properties of grafted polyesters were discussed. In the case of grafting of acrylics of more than 25% in the grafting product, mechanical properties of the grafting products decreased greatly compared with the raw polyester. The influence of the molecular structure of the grafted polyester was not observed. The effect of composition of the grafted polymers was discussed. Mechanical properties varied with the composition of the side chain. In the case of grafting onto aromatic polyesters, grafting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…First, we studied T 1pH of the P(EA‐AA)‐grafted polyesters. In a previous article,14 we reported that the blend of the ungrafted polyester and the P(EA‐AA) was immiscible. Figure 9 shows the decay time distributions of the main chain and the side chain of the P(EA‐AA)‐grafted polyester, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…First, we studied T 1pH of the P(EA‐AA)‐grafted polyesters. In a previous article,14 we reported that the blend of the ungrafted polyester and the P(EA‐AA) was immiscible. Figure 9 shows the decay time distributions of the main chain and the side chain of the P(EA‐AA)‐grafted polyester, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…In previous articles, we discussed the preparation and the characterization of an acrylics‐grafted polyester and its dispersion, i.e., the effect of the grafting conditions, reactivities of the grafting monomers, the grafting solvents,10 the grafting methods11 on the molecular structures of the grafted polyesters, the particle structures,13 the particle diameters of their dispersions,10 and the dispersion viscosity and the dispersion rheology 12. We discussed the mechanical properties of the acrylics‐grafted polyesters to make the factor effecting the mechanical properties clear in our previous article 14. The mechanical property of the acrylics‐grafted polyesters was effected by the composition of the grafted side chain (the acrylic segments), not the molecular weights of the grafted side chain or the content of the grafted side chains in grafted polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…They consist of "core-shell" particles with a core of high molecular weight polyester. Small particle diameters were obtained by use of polyesters having the largest amount of unsaturated bonds unless gelation occurs [24][25][26][27][28][29][30]. Thermosetting water based polyester resin coating composition prepared from polyalkadienediol may be directly applied to wet electrodeposited coating [31].…”
Section: Automotive Coating Layers 173mentioning
confidence: 99%
“…Polyester resin has some advantages such as good luster, high fullness, an easy to achieve high solid differentiation, and acrylic resin pollution resistance, good adhesion, light and color characteristics, so polyester modified acrylate has become a new research direction [18,19]. Schork et al [20] synthesized unsaturated polyester modified acrylic resin by a hybridization microemulsion polymerization, which was made into paint film with uniform luster.…”
Section: Introductionmentioning
confidence: 99%